2017
DOI: 10.1002/ange.201707274
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of [18F]Fluoroarenes by Nucleophilic Radiofluorination of N‐Arylsydnones

Abstract: Apractical method for radiofluorination of anilines with [ 18 F]fluoride via N-arylsydnone intermediates is described. These precursors are stable,e asy to handle and facilitate direct and regioselective 18 F-labeling to prepare [ 18 F]fluoroarenes.T he value of this methodology is further highlighted by successful application to prepare an 18 F-labeled neuropeptide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 76 publications
0
21
0
Order By: Relevance
“…In 2017, the Murphy group developed the first method to radiofluorinate anilines by converting them into N -arylsydnones, followed by nucleophilic attack by [ 18 F]fluoride ( Scheme 11 ). 62 The transformation is operationally simple and can be automated but can only be used for arenes bearing electron-withdrawing groups.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, the Murphy group developed the first method to radiofluorinate anilines by converting them into N -arylsydnones, followed by nucleophilic attack by [ 18 F]fluoride ( Scheme 11 ). 62 The transformation is operationally simple and can be automated but can only be used for arenes bearing electron-withdrawing groups.…”
Section: Discussionmentioning
confidence: 99%
“…[116] It was found that the sydnone was not only inductively more electron withdrawing than the nitro group,b ut was also positioned away from the aryl plane and limited full resonance with the arene.T his makes the sydnone aw eak anion stabilizer and an excellent activating group for 18 Fincorporation. [116] It was found that the sydnone was not only inductively more electron withdrawing than the nitro group,b ut was also positioned away from the aryl plane and limited full resonance with the arene.T his makes the sydnone aw eak anion stabilizer and an excellent activating group for 18 Fincorporation.…”
Section: Aromatic Nucleophilic Substitutionmentioning
confidence: 99%
“…A dozen 3/5-[ 18 F]fluoropyridines functionalized with electron donating or withdrawing substituents were thus obtained in 6− 78% isolated yields. The 13 C, 19 F, and 11 B NMR spectra were recorded on a Bruker Avance 400 or 500 MHz spectrometer. Samples were dissolved in an appropriate deuterated solvent (CDCl 3 , MeOD, or DMSO-d 6 ).…”
Section: ■ Conclusionmentioning
confidence: 99%
“…More recently, N-5-(2-cyanopyridinyl)sydnone was successfully converted to the corresponding 2-cyano-5-[ 18 F]fluoropyridine under harsh temperature conditions (150 °C) but no additional examples were reported. 13 The copper mediated radiofluorination of a pyridinylboronate ester precursor was attempted for the preparation of 2-chloro-5-[ 18 F]fluoropyridine, but yields did not exceed 10%. 14 The 18 F-deoxyfluorination approach via a concerted nucleophilic aromatic substitution (CS N Ar) was only reported from 3-hydroxypyridines bearing an electronwithdrawing group at an appropriate position.…”
mentioning
confidence: 99%